Resident’s perceived impacts on Kelantan International Kite Festivals: a qualitative enquiry - Ramely, Asmahany; Kayat, Kalsom; Mohd Nor, N. A. (Academic Research Publishing Group, 2018)
Kelantan International Kite Festival (KIKF) is hosted by Kelantan State Government annually as one of the many products to attract tourists and visitors to the state as well as to provide recreational activities to local residents. Since first hosting it 37 years ago, the state believes that the festival is an important showcase of Kelantan Malay tradition and cultural heritage. However, no systematic investigation has been undertaken, thus far to understand the perceptions held by local residents towards the festival. Understanding resident perceptions are crucial in the process of promoting any local resources, including cultural resource, in tourism development. Using qualitative data collected through in-depth interviews with the residents, this study examines residents‟ perceived impacts of KIKF. Specifically, this study was focused in understanding major impacts brought by KIKF as perceived by residents and whether these perceived impacts echo those mentioned by existing literature. Findings from this study indicate that respondents have the positive spirit with regards to KIKF especially because they perceive that KIKF has the potential to preserve their cultural traditions. This festival is something that the residents look forward for every year even when they know that the festival causes traffic congestion and that outsider are the ones benefitting from iteconomically